Evolutionary changes in symbiont community structure in ticks - Duron, Olivier; Binetruy, Florian; Noël, Valérie; Cremaschi, Julie; McCoy, Karen D.; Arnathau, Céline; Plantard, Olivier; Goolsby, John; Pérez de León, Adalberto A.; Heylen, Dieter J. A.; Van Oosten, A. Raoul; Gottlieb, Yuval; et al. (2017)
Ecological specialization to restricted diet niches is driven by obligate, and often maternally inherited, symbionts in many arthropod lineages. These heritable symbionts typically form evolutionarily stable associations with arthropods that can last for millions of years. Ticks were recently found to harbour such an obligate symbiont, Coxiella-LE, that synthesizes B vitamins and cofactors not obtained in sufficient quantities from blood diet. In this study, the examination of 81 tick species shows that some Coxiella-LE symbioses are evolutionarily stable with an ancient acquisition followed by codiversification as observed in ticks belonging to the Rhipicephalus genus. However, many other Coxiella-LE symbioses are characterized by low evolutionary stability with frequent host shifts and extinction events. Further examination revealed the presence of nine other genera of maternally inherited bacteria in ticks. Although these nine symbionts were primarily thought to be facultative, their distribution among tick species rather suggests that at least four may have independently replaced Coxiella-LE and likely represent alternative obligate symbionts. Phylogenetic evidence otherwise indicates that cocladogenesis is globally rare in these symbioses as most originate via horizontal transfer of an existing symbiont between unrelated tick species. As a result, the structure of these symbiont communities is not fixed and stable across the tick phylogeny. Most importantly, the symbiont communities commonly reach high levels of diversity with up to six unrelated maternally inherited bacteria coexisting within host species. We further conjecture that interactions among coexisting symbionts are pivotal drivers of community structure both among and within tick species.